Relevansi Batas Usia Perkawinan di Indonesia: Perspektif Madzhab Syafi’i dan Kompilasi Hukum Islam - Mawardi Mawardi; Varid Razak (Jurnal Multidisiplin Ibrahimy, 2024)
This research is motivated by the existence of age limits for marriage in Indonesia. The aim is for the common good in building a household built through a marriage bond, although in reality, early marriage can still be carried out by submitting a marriage dispensation through the courts for specific reasons. The focus of this research is: (1) How is the argument of the Syafi'i school of thought about the age limit for marriage; (2) How is the age limit for marriage in the Compilation of Islamic Law (KHI); and (3) The relevance of the age limit for marriage in Indonesia from the perspective of the Syafi'i School of Thought and the Compilation of Islamic Law. The type of research used in this research is library research, namely by using data from books or books that are in accordance with the title of the research as a source of study, along with reviewing and reading writings and books that are related to the object of discussion. The approach used by researchers in this writing is normative, in the sense of trying to examine the law that has been conceptualized as rules and norms that have been applied in society and become a legal reference for everyone. The results of this study, in the view of the Syafi'i School, the age limit for marriage is seen from maturity, namely when he has reached puberty. Among the signs for someone who has reached puberty is the release of semen for men, usually at the age of 12 years, and menstruation for women, usually at the age of 9 years, because for someone who has reached the nature of puberty and aqil, it means that they have become ahliyah al-ada' who can be burdened with the responsibilities of sharia such as muamalah and other transactions. On the other hand, the Compilation of Islamic Law has provided an age limit for marriage, namely 19 years for men and 16 years for women, because Indonesian scholars see several factors that limit the age of marriage, such as avoiding early marriage, which has a terrible impact on married couples. Regarding its relevance in its implementation in Indonesia, the age limit for marriage in the Compilation of Islamic Law has been determined. However, if you still want to marry under the age that has been determined, you must go through a trial process to request a marriage dispensation from the panel of judges. The opinion of the Syafi'i School can be a choice that can be considered by the panel of judges to approve a marriage dispensation, namely the adequacy of the age of puberty as one indicator of maturity.